Effects of N-NO-3 and N-NH+4 on the fresh and dry matter, on the nitrogen concentrations and on the nitrate reductase activity in Vigna unguiculata (L.) Walp - Lima Filho, Sebastião Alves de; Neptune, André Martin Louis (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1982)
This paper deals with studies, under field conditions, on the effects of the levels of nitric and ammonium fertilization on the production of fresh and dry matter, activity of nitrate reductase, total nitrogen and nitric concentrations in the vegetative parts and in the pulses. Two periods of sampling were adopted: a) at 90 days, for sampling of the vegetative parts; b) at the end of the vegetative cycle for grain sampling. In gene ral, the plants showed a better development with the N-NO-3 applications and better results in all the analisis fmass production, N-total, N-NO-3 and activity of NO-3, reductase), in the dry mass, fresh mass and grains,when compared with the same rates (0, 50, 100, 200 and 400 kg/ha), applied in the N-NH+4 form. The ammonium fertilizer worked, whithin certain limits, as an inhibitor agent of the enzymatic activity, specially at the rates of 200 and 400 kg/ha of N-NH+4. All treatments increased the N-total in the dry mass, and specially in the grains, showing an increase in the yield, independent of the N form applied. In treatments with high rates of N, there was a too high increase of the nitrate in the grains, which is a warrying factor,since these contents surpass the security limits for the health of human beings.